Reclamation Planning on Mining Operations PT. Prima Timah Utama in Mapur Village, Bangka Regency, Bangka Belitung Province - Imam Firdaus; Didik Susetyo; Restu Juniah (Indonesian Journal of Environmental Management and Sustainability, 2018)
PT. Prima Timah Utama is one of the companies that received a Production Operation Mining Permit from the Bangka Regency Government in May 2014. The company has been carrying out mining activities since Mei 2014, with a maximum production level of 500,000 m3 of ore per year. This study made a field study of the impact of mining activities carried out by the company, looked at the success rate of reclamation, and calculated the ideal costs to improve environmental quality after mining activities. Reclamation planning for mining operations at PT. Prima Timah Utama is included in the type of non-experimental qualitative research conducted desktop study and field observations in the mining field. This research will analyze and make a reclamation plan based on the criteria of success of ex-mining land that is standard for sustainable mining. The results of the study show a lack of guarantee of the implementation of reclamation guaranteed by the Company to the government of ± 50% of ideal conditions. Based on the results of the study, the company will use plants that are able to have a high level of adaptation to critical environments. One type of plant chosen is Acacia mangium. The costs needed to carry out the ideal reclamation activities to improve the quality of the environment after mining are IDR 3,642,427,321.- or IDR 65,629,324.- / hectare